2010
DOI: 10.1111/j.1472-4642.2009.00617.x
|View full text |Cite
|
Sign up to set email alerts
|

Profile or group discriminative techniques? Generating reliable species distribution models using pseudo‐absences and target‐group absences from natural history collections

Abstract: Aim  The presence‐only data stored in natural history collections is the most important source of information available regarding the distribution of organisms. These data and profile techniques can be used to generate species distribution models (SDMs), but pseudo‐absences must be generated to use group discriminative techniques. In this study, we evaluated whether the SDMs generated with pseudo‐absences are reliable and also if there are differences in the results obtained with profile and group discriminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
159
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(172 citation statements)
references
References 62 publications
6
159
1
6
Order By: Relevance
“…As true absences of Bd are not available, particularly in those insufficiently surveyed or undetected localities, and GLS models are susceptible to false absence data [38], we included Bd presence and pseudo-absences as the response variable in GLS models [38] (see the electronic supplementary material, appendix S5). We used AIC to compare the full GLS models to the pruned models and to compare models with FN variables alone to models with FN and PP [39].…”
Section: (C) the Evaluation And Validation Of Maxent Modelsmentioning
confidence: 99%
“…As true absences of Bd are not available, particularly in those insufficiently surveyed or undetected localities, and GLS models are susceptible to false absence data [38], we included Bd presence and pseudo-absences as the response variable in GLS models [38] (see the electronic supplementary material, appendix S5). We used AIC to compare the full GLS models to the pruned models and to compare models with FN variables alone to models with FN and PP [39].…”
Section: (C) the Evaluation And Validation Of Maxent Modelsmentioning
confidence: 99%
“…SDMs were computed with MAXENT 3.3.3k, applying default settings and a logistic output format (Phillips et al, 2006;Phillips and Dudík, 2008;Elith et al, 2011) and using a training area enclosed by a 100-km buffer around the species records (see recommendation by Mateo et al (2010)). To evaluate SDMs through the area under the receiver operating characteristic curve (Swets, 1988), a total of 100 SDMs were computed, each trained with 70% of the species records and tested with the remaining 30%.…”
Section: Species Distribution Modellingmentioning
confidence: 99%
“…Previous studies have indicated that generative methods give better predictions than discriminative methods (Phillips & Dudík, 2008). In addition, some authors have argued that the MaxEnt model approach performs better than other presence-based algorithms (Elith et al, 2006;Benito de Pando & Peñas de Giles, 2007;Elith & Leathwick, 2009;Mateo et al, 2010) and usually guarantees accurate predictions of species' distribution (Elith et al, 2006;Tsoar et al, 2007). Besides MaxEnt employs a regularization function that prevents prediction from over-fitting the data (Phillips et al, 2006;Phillips, 2008).…”
mentioning
confidence: 99%